2010
DOI: 10.1111/j.1365-2869.2009.00773.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of sympathetic function in the sleep-related change of gastric myoelectrical activity in rats

Abstract: SUMMARYThe gastric myoelectrical activity (GMA) fluctuates across sleep-wake states as a result of modulation by the brain-gut axis. The role of the autonomic nervous system in this phenomenon, however, was not elucidated fully. Through simultaneous recording and subsequent continuous power spectral analysis of electroencephalogram, electromyogram, electrocardiogram and electrogastromyogram (EGMG) in 16 freely moving Wistar rats, the sleep-wake states of the animals were defined and indices of cardiac autonomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
2

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 44 publications
1
7
2
Order By: Relevance
“…In this study, the range of the EGMG dominant frequency was similar to that reported in previous studies, 26,43 in which the sleep–wake states of the study subjects were not defined. In our previous study using Wistar rats, however, the frequency of gastric slow wave was slightly but significantly lower during QS 20 . This phenomenon was not observed in this study and might be ascribed to the different strain of rat used.…”
Section: Discussioncontrasting
confidence: 86%
See 4 more Smart Citations
“…In this study, the range of the EGMG dominant frequency was similar to that reported in previous studies, 26,43 in which the sleep–wake states of the study subjects were not defined. In our previous study using Wistar rats, however, the frequency of gastric slow wave was slightly but significantly lower during QS 20 . This phenomenon was not observed in this study and might be ascribed to the different strain of rat used.…”
Section: Discussioncontrasting
confidence: 86%
“…Fluctuations in EGMG power across the various sleep–wake states were observed in all four experimental groups, but the extent and pattern were different. In the Sham group, the power during AW was significantly higher than during the other two states, while the power during PS was significantly higher than during QS, as was reported in our previous study 20 . Either vagotomy or chemical sympathectomy alone did not abolish this pattern of change as it was preserved in both the TV and Sham + 6‐OHDA groups.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations